Scoping Review of Dental Management in Patients with Cardiovascular Disease: Roles of Local Anesthesia, Echocardiographic Assessment, Emergency Medical Support, nursing care ,Clinical Pharmacology, and Laboratory Medicine - Alyami, Mahdi Ali Mohameed; Shaker, Nouf Ahmed; Alshahrani, Tariq Abdulrahman; Abdulkareem, Khawlah Mohammed; Alatel, Haya Abdullah Rasheed; Al Alshihab, Abdullah Mohammed Saeed; Almousa, Nouf Adnan; Alsharhoof, Adeil Mahdi Ahmad; Alamri, Rahaf Mohammed; Alanazi, Rawan Mohammed Azzu (Journal of Posthumanism, 2024)
Dental management of patients with cardiovascular disease (CVD) presents unique challenges that require interdisciplinary awareness and clinical adaptation. Cardiovascular conditions such as ischemic heart disease, arrhythmias, and anticoagulant use may complicate routine dental care and elevate procedural risks.This scoping review aims to map and synthesize recent evidence (2015–2024) on dental care practices for patients with CVD, focusing on five domains: local anesthesia, echocardiographic assessment, emergency medical support, clinical pharmacology, and laboratory medicine.A comprehensive literature search was conducted across databases including PubMed, Scopus, and Web of Science. Studies were included if they addressed dental procedures in CVD patients and related to any of the five thematic domains. Data were charted and thematically analyzed following the PRISMA-ScR framework.Sixty-seven studies were included. Local anesthesia with vasoconstrictors was deemed generally safe in stable cardiac patients when used judiciously. Echocardiographic assessments, though infrequent, aided risk stratification in medically complex cases. Emergency preparedness was often insufficient, with limited access to AEDs or trained staff. Continuation of direct oral anticoagulants during dental procedures was widely supported, although clinician coordination was critical. Laboratory tests such as INR and renal function assessments were useful in managing bleeding and drug clearance risks.Dental care for patients with cardiovascular disease demands tailored protocols, multidisciplinary collaboration, and improved clinical infrastructure. In Saudi Arabia, integrating emergency preparedness, medication reconciliation, and national guidelines into dental practice is essential to improve patient safety and standardize care.